(untitled) (Eurasian Journal of Philology Science and Education, 2018)
The article examines the I. Shmelev’s stories about the provincial life, in which the writer develops the traditions of Russian classical literature. The provincial chronotop has an aesthetic significance for him and becomes material for the plots. The life of the province is a recurring theme in Shmelev’s prose. The spatial structure of the works can be described as a soulless space, separated from the rest of the world, where life is characterized by the limited physiological needs of the characters. The writer’s method based on realistic traditions and demonstrates the ability to update An artistic whole of his prose is a complex interaction of realism and modernism. Shmelev’s writing remains as ‘dense’ as the one of his early works, but a new style is embodied in the stories. The writer is attached to the artistic quest of the early XX-th century, he actively uses the modernist’s artistic techniques and new ways of composition. ‘Symbolic component’ reflects the new thinking and the renewal of poetics in the Russian realism of the early XX-th century.